MECHANISMS FOR MITIGATING THE NEGATIVEEFFECTS OF GADGET USE AMONG ADOLESCENTS:INTERNATIONAL EXPERIENCE - Akramova Gulrukh Alihanovna (Euro Asian Journal Publishing, 2026)
This article examines the mechanisms for mitigating the negative effects of gadget use among adolescents based on the experience of foreign countries. The study analyzes the social, psychological, and educational risks associated with excessive use of digital devices. Special attention is paid to preventive strategies implemented in developed countries, including parental control systems, digital literacy programs, school-based regulations, and psychological support measures. The article also highlights the role of cooperation between educational institutions, families, and society in promoting the rational and safe use of gadgets among adolescents
Keywords: Adolescents; gadget use; negative effects